Melatonin-loaded nanocarriers: New horizons for therapeutic applications - Chuffa, Luiz Gustavo de Almeida [UNESP] (2021)
The use of nanosized particles has emerged to facilitate selective applications in medicine. Drug-delivery systems represent novel opportunities to provide stricter, focused, and fine-tuned therapy, enhancing the therapeutic efficacy of chemical agents at the molecular level while reducing their toxic effects. Melatonin (N-acetyl-5-methoxytriptamine) is a small indoleamine secreted essentially by the pineal gland during darkness, but also produced by most cells in a non-circadian manner from which it is not released into the blood. Although the therapeutic promise of melatonin is indisputable, aspects regarding optimal dosage, biotransformation and metabolism, route and time of administration, and targeted therapy remain to be examined for proper treatment results. Recently, prolonged release of melatonin has shown greater efficacy and safety when combined with a nanostructured formulation. This review summarizes the role of melatonin incorporated into different nanocarriers (e.g., lipid-based vesicles, polymeric vesicles, non-ionic surfactant-based vesicles, charge carriers in graphene, electro spun nanofibers, silica-based carriers, metallic and nonmetallic nanocomposites) as drug delivery system platforms or multilevel determinations in various in vivo and in vitro experimental conditions. Melatonin incorporated into nanosized materials exhibits superior effectiveness in multiple diseases and pathological processes than does free melatonin; thus, such information has functional significance for clinical intervention.